Modern logistics systems and their efficiency - Gofurova Lola (THE INNOVATION ECONOMY, 2026)
This article analyzes modern logistics systems and methods to improve their efficiency. It examines the main components of logistics systems, including transportation, storage, inventory management, supply chain management, and information systems. The study also highlights the role of modern technologies such as ERP, IoT, GPS monitoring, and automated warehouse systems in logistics processes. The article provides practical examples from international (Amazon, DHL) and local companies, demonstrating how logistics systems function in real conditions and how efficiency can be enhanced. The results indicate that implementing effective logistics systems is crucial for reducing costs, shortening delivery times, and providing high-quality service to customers.